Building a School Guest Book Information System Using the Waterfall Method - Muhammad Subhana (bit-Tech, 2025)
The increasing volume of data on human activities has resulted in a growing number of visitors to schools, particularly in the western part of Rangkasbitung, Lebak, Banten. Prospective parents visit the RA (Raudhatul Athfal) institution to enroll their children in school, pay monthly administration fees, and engage in educational activities with various general visitors. This influx poses several challenges for school administration and security, especially since visit records are still maintained manually, leading to data loss, difficulties in accessing visit histories, and limitations in monitoring guests, including parents and vendors. This issue impacts the transparency of school activity records. To address this, the research proposes a web-based school booking system to record visitor data based on the purpose of the visit, thus allowing for more effective data access and preliminary analysis in the event of an incident. This system is developed using the waterfall method, which is chosen for its structured concept, suitable for small to medium-sized school environments. Each phase consists of needs analysis, design, implementation, testing, and maintenance, carried out sequentially. Evaluation using a Likert scale from 104 respondents (determined by Slovin's formula) showed the Daily Report feature scored highest at 3.81, while the Weekly Report was lowest at 3.04. Maintenance tests found input validation and weekly report printing less smooth (2.84 and 2.69). Overall, the system effectively supports visitor monitoring with accessible features.